2017
DOI: 10.1002/jrs.5089
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman optical activity of zeaxanthin aggregates

Abstract: New methods of enhancement in Raman optical activity (ROA) scattering are of great interest. So, previously reported by us, Aggregation-Induced Resonance ROA (AIRROA) may open new opportunities in a field of structural studies of many biologically important compounds. However, the AIRROA phenomenon, reported up until now for astaxanthin and lutein derivatives, requires a deeper understanding and investigation of other carotenoids. Zeaxanthin is a dominant macular pigment that protects human retina against phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…[7,8] According to this effect, as mall number of chiral units (sergeants) force al arge number of achiral ones (soldiers) to adopt asupramolecular structure and to display an intense chiral signal. [20][21][22][23] Those assemblies also show strong optical activity,g enerated by the non-symmetric layout of molecules through non-covalent interactions (p-p stacking, hydrogen bonding,h ydrophobic effects). [17][18][19] Thec hirality of the model aggregates studied is due to chirality transfer between chiral aCo ra staxanthin (AXT) molecules and achiral bC components,w hich together form am ixed supramolecular chiral system exhibiting resonance-enhanced ROA(RROA).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[7,8] According to this effect, as mall number of chiral units (sergeants) force al arge number of achiral ones (soldiers) to adopt asupramolecular structure and to display an intense chiral signal. [20][21][22][23] Those assemblies also show strong optical activity,g enerated by the non-symmetric layout of molecules through non-covalent interactions (p-p stacking, hydrogen bonding,h ydrophobic effects). [17][18][19] Thec hirality of the model aggregates studied is due to chirality transfer between chiral aCo ra staxanthin (AXT) molecules and achiral bC components,w hich together form am ixed supramolecular chiral system exhibiting resonance-enhanced ROA(RROA).…”
mentioning
confidence: 99%
“…[9,10] This kind of chirality amplification has been observed for other supramolecular systems, [11][12][13] such as foldamers, [14] helical nanotubes and columns, [15,16] as well as polymers and copolymers. [20][21][22][23] Nevertheless,R OA spectroscopy is hampered by its low sensitivity because only one photon in ab illion gives rise to the ROAe ffect. On the other hand, aggregates composed of only chiral carotenoids had been studied by us before.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, they analyzed two types of chiral zeaxanthin self‐assembly, H and J1, and concluded that an aggregation process is not enough to enhance the ROA signal. Essential for the aggregation induced RROA effect is that the electronic circular absorption band of supramolecular species is in proximity with the ROA excitation line . Mensch et al presented the ROA of human α‐synuclein in intrinsically disordered, micelle‐bound α‐helical, molten globule and oligomeric β‐sheet states.…”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…Essential for the aggregation induced RROA effect is that the electronic circular absorption band of supramolecular species is in proximity with the ROA excitation line. [246] Mensch et al presented the ROA of human α-synuclein in intrinsically disordered, micelle-bound α-helical, molten globule and oligomeric β-sheet states. Alphasynuclein (α-syn) is a 140-residue protein that plays a central role in Parkinson's disease and other neurological disorders.…”
Section: Raman Optical Activitymentioning
confidence: 99%